The effect of special exercises on the speed of motor response and performance of the snatch skill for wrestling players under (16) years old - Shihap, Ammar; Ahmed , Samer (Journal of Physical Education, 2025)
The problem of the research is that the level of performance of wrestling players is not at the required level, and from the researcher’s point of view, he believes that one of the reasons for this is due to the weakness of the player’s response speed, since wrestling requires a quick reaction, through which the wrestler’s level of skill performance can improve. The research aimed to prepare special exercises and know their effect on the speed of motor response and performance of the snatch skill for wrestling players aged under (16) years old. It was assumed that there are statistically significant differences between the experimental and control groups in the post-tests in both the speed of motor response and the level of performance of the snatch skill. The researcher used the experimental method by designing two equivalent experimental and control groups with a pre-test and post-test, on a sample of wrestling players under (16) years old, numbering (14) players. The variable of response speed and snatch skill in wrestling was tested for the research sample after the completion of the main experiment. After processing the data statistically, the researcher concluded that the exercises prepared by the researcher proved effective in improving the speed of motor response and the snatch skill of the players.